Blunted heart rate recovery is associated with coronary artery spasm in patients with suspected vasospastic angina - Hyunsu Kim; Sang-Hoon Cho; Kyoung-Im Cho; Bong-Joon Kim; Sung-Il Im; Jung-Ho Heo (BMC, 2017)
Abstract Background Autonomic nervous system activity has been shown to be altered in patients with vasospastic angina (VA). Heart rate recovery (HRR) is a simple, non-invasive measurement of autonomic nervous system dysfunction. We aimed to investigate whether HRR is related to VA, as established by an ergonovine test. Methods A total of 976 consecutive patients (47.5% male, mean age 55 years) without significant coronary artery disease who underwent both an ergonovine provocation test and a treadmill exercise test were enrolled. The relationship between VA and HRR was evaluated. Results A total of 30.7% (300/976) of patients were diagnosed with VA, as documented by the ergonovine provocation test. HRR was significantly reduced in patients with VA compared to patients without VA (24.6 ± 18.0 vs. 30.5 ± 22.2, p < 0.001), and HRR was lowest in patients with multi-vessel spasm (21.9 ± 17.3). The proportion of blunted HRR, which was defined as HRR less than 12 beats, was significantly higher in patients with VA than in those without coronary artery spasm (26.6% vs. 39.3%, p < 0.001). In multivariable regression analyses, age (odds ratio (OR) = 1.03; 95% confidence interval (CI): 1.01-1.04; p = 0.001), blunted HRR (OR = 1.71; 95% CI: 1.26-2.31; p < 0.001), current smoking status (OR = 2.11; 95% CI: 1.50-2.98; p < 0.001), and male gender (OR = 2.00; 95% CI: 1.43-2.78; p < 0.001) were significant independent predictors of VA presence. Conclusion Blunted HRR was an independent predictor of VA presence, which suggests a link between coronary artery spasm and autonomic dysregulation.